Design of phase matching chessboard‐like electromagnetic metasurfaces for wideband radar cross section reduction. Issue 9 (13th April 2019) - Chen, Haiyan; Shen, Rongbo; Li, Fengxia; Zhou, Yang; Zhang, Li; Weng, Xiaolong; Lu, Haipeng; Xie, Jianliang; Deng, Longjiang
Abstract: In this article, a chessboard‐like electromagnetic metasurfaces which can realize the polarization compensation and cancellation of the reflection beam in microwave region is designed and realized for wideband radar cross section (RCS) reduction. The chessboard‐like electromagnetic metasurfaces are composed of a square annular artificial magnetic conductor (AMC) combination with the Jerusalem cross AMC. Simulation and experimental results demonstrate that the chessboard‐like electromagnetic metasurfaces exhibit significantly RCS reduction over −10 dB in the frequency bandwidths 6.16‐18 GHz, and two RCS reduction peaks at 7.0 and 12.0 GHz in the considering frequency ranges for the normal incidence of an electromagnetic wave. The physical mechanisms of the RCS reduction peaks can be elucidated by the phase matching technology similar to the impedance matching technology applied to radar absorbing materials (RAMs). The basic physical property implies that RCS reduction based on the composite AMC metasurfaces can be improved greatly by introducing as many phase matching points as possible in the functional frequency bands. Considered that the phase matching is a necessary condition rather than a sufficient condition for RCS reduction of the chessboard‐like AMCs structures, other physical mechanisms of RCS reduction are also discussed by far field distribution, near field distribution and the properties of mono‐static RCS reduction.